Sensitive and specific immunodetection of human glandular kallikrein 2 in serum. - Becker, C; Piironen, T; Kiviniemi, J; Lilja, H; Pettersson, K (2000)
BACKGROUND: Human glandular kallikrein 2 (hK2) is expressed in the prostate and is present in serum from men with prostate cancer. Specific detection in serum is difficult mainly because of low concentrations and immunological cross-reactivity with prostate-specific antigen (PSA). Our objectives were to design an assay with improved analytical detection and functional sensitivity and nonsignificant cross-reactivity with PSA, and to characterize different immunoreactive forms of hK2. METHODS: In the assay, critical PSA epitopes were blocked with four monoclonal antibodies (MAbs) specific for PSA. Subsequently, hK2 was captured using a MAb against hK2 (5% cross-reactivity with PSA), and after washing, hK2 was detected by a europium-labeled MAb with identical affinity for hK2 and PSA. RESULTS: The analytical detection limit was <10 ng/L, and functional sensitivity was 30 ng/L. Cross-reaction with PSA was <0.01%. Between-assay imprecision was 3.1% for 1600 ng/L hK2 and 4. 8% for 160 ng/L hK2; corresponding values for within-assay precision were 1.9% and 4.5%, respectively. Complexes of hK2-alpha(1)-antichymotrypsin (ACT) were detected in vitro with -6% bias compared with the free form of hK2. Gel filtration of patient samples showed that hK2 correlated in size mainly with free hK2; only 4-19% corresponded to hK2 possibly complexed with ACT or protein C inhibitor. CONCLUSIONS: Our assay had extremely low cross-reactivity with PSA, provided a very low detection limit, and allowed close to equimolar detection of the free and complexed forms of hK2. Moreover, we found that free hK2 is the predominant immunoreactive form of hK2 in serum.